Characterization of Cha-Kram leaf extract powder using ultrasound-assisted extraction and its application in gelatin-based film as biodegradable active film - Pudthaya Kumnerdsiri; Sasina Sanprasert; Jantana Praiboon; Anusorn Seubsai; Wanchat Sirisarn; Jaksuma Pongsetkul; Nathdanai Harnkarnsujarit; Saroat Rawdkuen; Supatra Karnjanapratum; Samart Sai-Ut; Passakorn Kingwascharapong (Future Foods)
Poor management of plastic waste leads to environmental pollution, a problem that has been tackled by introducing biodegradable plastic containing bioactive compounds, as an alternative to traditional plastics. This research investigated the effects of different solvents (water or ethanol) and ultrasonic extraction conditions (ultrasonic power: 30 %, 60 %, or 90 %; extraction times: 15 or 30 min) on the physical and functional properties of dechlorophylled Cha-Kram leaf extract powder (DCKLEP). The highest antioxidant activities were extracted using 60 % ultrasonic power and 30 min of extraction time (60 % DCKLEP-alc 30 min). In addition, the effects of different concentrations of 60 % DCKLEP-alc 30 min (0, 0.375, 0.75, 1.5, or 3 %) on the attributes of gelatin films were evaluated. The results indicated that increasing the 60 % DCKLEP-alc 30 min concentration significantly (p < 0.05) enhanced the thickness, mechanical and thermal properties, light barrier properties, and antioxidant activities of the film. The structure of the film was modified due to the interactions between gelatin and 60 % DCKLEP-alc 30 min, as confirmed using FTIR analysis. The antioxidant activities and UV–visible light barrier property were improved by increasing the 60 % DCKLEP-alc 30 min concentration in the film. Thus, gelatin film containing 60 % DCKLEP-alc 30 min could potentially serve as an environmental-friendly, active film.